Dedicated exhaust gas recirculation applied to a rich burn industrial natural gas engine - Van Roekel, Chris, author; Olsen, Daniel B., advisor; Jathar, Shantanu, committee member; Marchese, Anthony, committee member; Young, Peter, committee member (Colorado State University. Libraries, 2020)
Rich burn natural gas engines provide power for industrial applications such as gas compression. In this application where exhaust oxides of nitrogen (NOx) requirements can be critical, rich burn engines offer best in class aftertreatment emission reduction and operating cost capabilities by using a non-selective catalyst reduction (NSCR) or three-way catalyst system. However, due to high combustion temperatures associated with near stoichiometric air-fuel ratio (AFR) operation, rich burn engines are limited in brake mean effective pressure (BMEP) by combustion temperature. Consumers in the gas compression application are left to choose between engines that are capable of meeting even the most stringent emission requirements (rich burn) and engines with high BMEP rating (lean burn). Charge dilution by way of excess air (lean burn) or exhaust gas recirulation (EGR) is a common method used to lower combustion temperature with the purpose of limiting the production of engine out NOx. Conventional configurations of EGR consist of high pressure loop (HPL) and low pressure loop (LPL), each of which rely on components exposed to relatively high temperatures to control the impact that EGR has on combustion. Dedicated EGR is a novel variant of conventional EGR configurations which allows for the impact that EGR has on combustion to be controlled by components exposed to ambient temperature natural gas while also lowering rich burn combustion temperatures. Due to the lack of published research on dedicated EGR applied to industrial natural gas engines and consumer driven need for technologies to increase rich burn industrial natural gas engine BMEP this work represents an initial investigation into challenges associated with and capabilities of dedicated EGR. A Chemkin chemical kinetics model using the SI Engine Zonal, Flame Speed Calculator, and Equilibrium models was developed to quantify dedicated cylinder exhaust composition, laminar flame speed, and equilibrium combustion composition, respectively. The Aramco 2.0 mechanism was used for natural gas kinetics and was modified to include Zel'dovich mechanism for NOx formation. Engine experiments were conducted using a Caterpillar G3304 rich burn natural gas engine modified to operate with and without dedicated EGR. Initial tests that included power sweeps at fixed dedicated cylinder AFR revealed that operating conditions appropriate for dedicated EGR gasoline engines were not suitable for dedicated EGR natural gas engines. A response surface method (RSM) optimization was performed to find improved operating conditions at part load, 3.4 bar BMEP. Results showed that advanced spark timing and slightly rich dedicated cylinder AFR were optimal to achieve decreased coefficient of variance of indicated mean effective pressure (COV IMEP) and balanced cylinder IMEP output. In order to assess how operating with dedicated EGR would affect the performance of a NSCR system at 6.7 bar BMEP and fixed operating conditions engine AFR was swept between rich and lean conditions to quantify catalyst reduction efficiency and find the emissions compliance window. Without intentional AFR dithering the emissions compliance window was increased significantly. Finally, using best operating conditions from the RSM optimization and engine AFR sweep tests engine BMEP was increased beyond the 6.7 bar rating to find the possible increase in power density resulting from dedicated EGR.
Keywords: natural gas engine; dedicated EGR; rich burn